Implementasi Penggunaan Media Ajar Berbasis Mixed-Media Pada Mata Pelajaran Geografi Di Kelas XI-H MAN 2 Blitar - Firnanda Riva Teresya; Yudi Krisno Wicaksono (Pusat Riset dan Inovasi Nasional, 2024)
Learning media is a medium used to convey information in the learning process in the educational sphere, so that effective communication between teachers and students will be formed.. The learning media used by teachers in Geography subjects is mixed-media based in the form of PowerPoint and YouTube. The research was carried out at MAN 2 Blitar school because it is the only superior madrasa in Wlingi district.. The problems that researchers found were based on pre-research results, students' lack of understanding of the material presented and lack of learning outcomes. There are several problem formulations based on the results of researcher observations, namely: 1) How is the use of mixed-media based teaching media in Geography subjects in class XI-H MAN 2 Blitar?, 2) What are the obstacles and challenges in using mixed-media based teaching media in Geography subject in class XI-H MAN 2 Blitar?, 3) What is the impact of using mixed-media based teaching media on Geography subjects in class This research uses qualitative research with a descriptive approach. Data collection techniques use interviews, observation and documentation. The results obtained by researchers are that mixed media is often used to support success in the learning process, so teachers must increase creativity to apply interesting learning media. Sometimes the internet connection network becomes an obstacle to the learning process. Even though mixed media is often used, there are still students who show boredom in learning.